Memo from Jane Tolmach - Jane Tolmach:::::: (1967)
A memo from Jane Tolmach that summarizes a November 9 meeting of the Women's Division Executive Board of the Democratic State Central Committee. Robert Coate spoke about his trip to Vietnam in support of President Johnson's views, and Joyce Fadem outlined plans for the statewide campaign kickoff conference, with members urged to assist and begin fundraising for the 1968 election. The memo also reports on several successful and upcoming Women's Division events across various congressional districts, highlighting strong participation and continued organizational activity.